On the origin of non-specific binders isolated in the selection of phage display peptide libraries - Bakhshinejad, Babak; Kjaer, Andreas (Frontiers in Microbiology, 2025)
Over the recent decades, phage display has been used successfully to identify a variety of peptides with diagnostic and therapeutic applications. Despite the significant role of this technology in the pharmaceutical industry, the affinity selection of phage display peptide libraries through biopanning suffers from some limitations. The most significant drawback of phage display is the undesirable enrichment and isolation of phages whose displayed peptides have no binding affinity toward the target. Phages with high amplification rates constitute the most important category of non-specific binders. Amplification, which aims to increase the copy number of phages displaying target-specific peptides, acts like a double-edged blade and can also make a major contribution to the target-unrelated enrichment of non-specific binders, leading to compositional bias in the sequence content of the biopanning output. The cutting-edge breakthroughs fueled by the integration of next-generation sequencing (NGS) into phage display have led researchers to gain a deeper understanding of the information content of the phage population recovered from biopanning and how its peptide content changes during further rounds of selection and amplification. This body of vastly increasing information has shed more light on the complications encountered during library selection and opened new perspectives to obtain in-depth insights into amplification-associated bias in the selected phage display libraries, analyze biopanning data more rigorously, and devise more optimal protocols for phage display selections. This knowledge can finally provide a solid foundation for discovering promising target-specific binders in the evolutionary selection of phage display libraries.